Lessons Learned: Achieving Consensus About Learning Disability Assessment and Diagnosis. (September 2022) - Williams, Tricia; Wiener, Judith; Lennox, Carolyn; Kokai, Maria
The current paper describes the process used for developing the Guidelines for Diagnosis and Assessment of Children, Adolescents, and Adults with Learning Disabilities-Consensus Statement and Supporting Documents, and the rationale for some of the decisions. The guidelines were developed by a cross-sectoral working group of psychologists who achieved a consensus on the criteria for diagnosis and the assessment process. We outline key features of the guidelines, describe topics where the group achieved consensus quickly and topics for which there was considerable debate (e.g., intelligence testing, ability/achievement discrepancy, and processing deficits). The group members shared information with each other about topics such as the advantages of early assessment, the importance of formally assessing effort and motivation, and assessment of culturally and linguistically diverse individuals. We conclude with the lessons learned and professional challenges regarding contextual influences on LD assessment and diagnosis and dissemination of research to practitioners.